Mikrostruktura, duktilnost in spinodalno razmešanje v zlitinah Fe28Cr10-16Co - Vodopivec, Franc (Kovine zlitine tehnologije, 1995)
In spite of relatively simple basic composition technical iron-chromium-cobalt alloys for permanent magnets are a complex material. Only with a careful control of impurities and the addition of secondary alloy elements the formation of phases ?$γ$? and ?$σ$? is prevented and a microstructure of ferromagnetic phase ?$α$? is obtained. A proper combination of thermal treatment for spinodal decomposition and a wire drawing deformation producing magnetic anisotrophy gives the best magnetic properties. The alloys are brittle by room temperature and the deformation is performed at increased temperature, where twinning is replaced by shearing deformation.
Keywords: Metallurgical and Materials Engineering; metalurgija; železove zlitine; zlitine; mikrostruktura; magnetne lastnosti; duktilnost